Foreign direct investment in development in developing economies and Turkey; the role of institutions - Dumludağ, Devrim. (Thesis (Ph.D.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2007., 2007)
The aim of this dissertation is to investigate the relationship among foreign direct investment and institutions in developing countries. In this dissertation I examine the role of macroeconomic variables and institutions as determinants of foreign direct investment flows by applying panel data regressions in developing economies. In addition, I apply a questionnaire survey to the executives of 52 multinational corporations operating in Turkey in order to reveal the impact of institutional variables on foreign direct investment.
Keywords: Investments, Foreign -- Developing countries.; Investments, Foreign -- Turkey.